SCIENTIFIC MIRACLES OF GRAPES IN THE QUR’AN AND HADITH: Perspectives on Religious Studies and Herbal Treatment - Atabik, Ahmad; Hamidah, Luluk (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
The fruit frequently mentioned in the Qur’an and hadith is grape. The term inab is cited eleven times in the Qur’an in relation to the numerous joys that Allah grants to His adherents in this world as well as in the afterlife. In his work al-Tibb al-Nabawi, Ibn Qayyim al-Jauziyah cited grape as a type of fruit that the Prophet consumed and that could be used as a remedy. Referring to the previous points of view, this study aims to explore the scientific miracles of grapes in terms of hadith and scientific interpretation, as well as to correlate them with religious scientific studies and herbal treatment using grapes. Grapes have drawn the attention of Muslims and western academics to investigate the content, benefits, and features of grapes as a fruit mentioned 11 times in the Qur’an, as a type of fruits consumed by the Prophet, as well as utilized as a treatment method. Grapes have the highest vitamin contents, including vitamin A, B, and C. Grapes have high mineral contents, with potassium reaching 62%, calcium, magnesium, phosphorus, iron reaching 2.182%, acid and phosphorus reaching 17%. According to several scientific studies, grapes are said to be capable of treating cough, cleansing intestines, aiding digestion, purifying blood, and even benefiting those with gastric disorders. Grapes can also be used as a medication to support respiratory treatment.[Buah yang sering disebutkan dalam al-Qur’an dan hadis adalah anggur. Istilah inab disebutkan sebelas kali dalam al-Qur’an sehubungan dengan banyaknya kenikmatan yang Allah berikan kepada para pengikut-Nya di dunia ini maupun di akhirat. Dalam karyanya al-Tibb al-Nabawi, Ibnu Qayyim al-Jauziyah menyebut anggur sebagai salah satu jenis buah yang dikonsumsi Nabi dan bisa dijadikan obat. Mengacu pada pandangan sebelumnya, kajian ini bertujuan untuk menjelaskan tentang mukjizat ilmiah buah anggur dalam tafsir ilmi maupun hadis, dan menghubungkannya dengan riset ilmiah keagamaan dan pengobatan herbal menggunakan anggur. Sebagai buah yang disebut 11 kali dalam al-Qur’an dan anggur juga termasuk jenis buah yang pernah disantap Nabi dan bisa digunakan sebagai sarana pengobatan, anggur menjadi perhatian para sarjana muslim maupun barat untuk meneliti kandungan, manfaat dan khasiat yang dimiliki oleh anggur. Anggur merupakan buah yang paling kaya kandungan vitaminnya, khususnya vitamin A, B, dan C. Kandungan mineral anggur pun cukup tinggi, yaitu potassium yang mencapai 62%, kalsium, magnesium, fosfor, dan zat besi yang mencapai 2,182%, asam dan fosfor sebanyak 17%. Dalam pelbagai penelitian ilmiah, anggur diyakini dapat mengobati batuk, membersihkan usus, pencernaan, memurnikan darah, bahkan bermanfaat untuk orang-orang yang terkena penyakit lambung. Anggur juga memiliki manfaat sebagai obat untuk mendukung pengobatan pernafasan.]